Efektivitas Pijat Refleksi dalam Mengurangi Fatigue Pasien Kanker: A Systematic Review - Wahyuni Arni; Selviana Tawil; Kadek Ayu Erika; Mulhaeriah Mulhaeriah (School of Nursing, Faculty of Medicine, Lambung Mangkurat University., 2022)
Fatigue is a common symptom associated with cancer and its treatment. It is also that can affect daily activities and quality of life of the sufferer. Reflexology is a complementary therapy that is increasingly being used as adjunct therapy alongside conventional and pharmacological treatments in cancer patients.Objective: to evaluate the effect of reflexology on fatigue in cancer patients. Methods: A systematic review was performed using an electronic database and a manual search of all studies reporting the effects of reflexology on the fatigue of cancer patients. A total of 10 studies were eligible for review, including 7 randomized control trial (RCT) designs and 3 experimental study designs. Results: A total of 1093 participants from 10 studies were analyzed in this systematic review. The included studies consisted of seven RCT trials and three quasi-experiments. We found a positive effect of reflexology in reducing fatigue in cancer patients. Conclusion: This review provides strong evidence regarding the ability of reflexology therapy to relieve fatigue in cancer patients. The results of this review provide nurses with an even better understanding of the effects of reflexology and have a better decision-making process for this intervention